2006
DOI: 10.1016/j.bbamem.2006.07.007
|View full text |Cite
|
Sign up to set email alerts
|

The human beta-defensin-3, an antibacterial peptide with multiple biological functions

Abstract: A group of interesting molecules called defensins exhibit multiple functions but have been primarily recognized to possess a broad spectrum of antimicrobial activities. Studies have reported two different types of defensins (alpha and beta) from human and animals, a cyclic theta defensin from rhesus, and several defensin-like peptides from plants. There is no amino acid sequence homology between these peptides, but they all contain three Cys-Cys disulfide linkages while the connectivities are different. Human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
237
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 299 publications
(250 citation statements)
references
References 132 publications
4
237
0
4
Order By: Relevance
“…This may have occurred because of differences in the concentration of hBD3 and Defb14 used, although the concentration of 20 μg/ml defensin used in our study was not excessively higher than that at which antimicrobial activity was observed (10). Additionally, different pathways may function, if the tumors themselves overexpress defensin (15,27).…”
Section: Figure 3 Time Dependency Of Cellular Damage Induced By Humamentioning
confidence: 64%
See 1 more Smart Citation
“…This may have occurred because of differences in the concentration of hBD3 and Defb14 used, although the concentration of 20 μg/ml defensin used in our study was not excessively higher than that at which antimicrobial activity was observed (10). Additionally, different pathways may function, if the tumors themselves overexpress defensin (15,27).…”
Section: Figure 3 Time Dependency Of Cellular Damage Induced By Humamentioning
confidence: 64%
“…In contrast to other defensin isoforms, the prominent features of hBD3 antimicrobial activity are its salt-independency and its broad antimicrobial spectrum (7,10,11).…”
mentioning
confidence: 99%
“…These peptides include two or more positively charged residues provided by arginine, lysine or, in acidic environments, histidine, and a large proportion (generally>50%) of hydrophobic residues. The secondary structures of these molecules follow 4 themes, including i) α-helical ii) β-stranded due to the presence of 2 or more disulfide bonds, iii) beta-hairpin or loop due to the presenc of a single disulfide bond and/ or cyclization of the peptide chain, and iv) extended 9 . Many of these peptides are unstructured in free solution, and fold into their final configuration upon partitioning into biological membranes.…”
Section: Introductionmentioning
confidence: 99%
“…The antimicrobial activity is explained by the ability to the HBD2, for example, to inhibit the LPS action and block the inflammation by the LPS-induced TNF-α production [25]. The similar way HBD3 is able to neutralize LPS 26], besides an in vitro study with S. aureus showed that its action is in the plasma membrane since it has the capability to cause morphological changes in the peripheral cell wall [21]. Moreover, HBD3 has a broad spectrum of antimicrobial activity against several pathogenic bacteria at low concentrations and independent of the sodium concentration [21].…”
Section: Introductionmentioning
confidence: 99%